(untitled) (Publications Office, 2025)
Contemporary leadership goes beyond mere technical management to become an exercise in service and social transformation—a premise that underpins the twelfth issue of Andina magazine. In an environment marked by a crisis of institutional trust and the complexity of democratic challenges, this publication proposes a return to ethics and strategic vision as drivers of change. Leadership is not defined here by hierarchy, but by the ability to positively influence reality and others through consistency and responsibility.